A critical analysis of past and present campaigns to challenge online racism in English professional football - Kilvington, Daniel (Hate crime in football, 2023)
Although racism in football stadiums has generally decreased over the last two decades, social media has provided a platform for individual fans and the far Right to racially abuse players, clubs and fans in relative safety. In 2022, The Alan Turing Institute released a report which tracked abuse on Twitter towards Premier League players across the 2021/22 season. Their machine learning tool found that there were 59,871 abusive tweets directed at Premier League footballers, with 68 per cent of players receiving abuse at least once. So, what is English football doing to challenge this and protect its players? This chapter begins by showcasing the findings from Kearns et al’s (2022) scoping review of sport, social media and hate, completed as part of a research project entitled Tackling Online Hate in Football. The review found that a total of 41 peer-reviewed articles were published in this field since 2005, with football receiving the most attention. The scoping review found that Twitter was the platform most examined, and racism was the most researched issue. Building on this, the chapter first contextualizes the existing research, including a focus on football-related online racism and a theorization of factors underpinning online racism. This provides a suitable backdrop for the next part of the chapter, where we critically analyse several campaigns and strategies used by key stakeholders to curb online racism and wider forms of discrimination in football. In our final summary, we put forward some ideas and countermeasures to challenge online racism in football.